Efficacy and Safety of Pembrolizumab in Patients Enrolled in KEYNOTE-030 in the United States: An Expanded Access Program. Issue 9 (November 2017) - Gangadhar, Tara C.; Hwu, Wen-Jen; Postow, Michael A.; Hamid, Omid; Daud, Adil; Dronca, Roxana; Joseph, Richard; O'Day, Steven J.; Hodi, F.S.; Pavlick, Anna C.; Kluger, Harriet; Oxborough, Romina P.; et al.
Abstract : KEYNOTE-030 (ClinicalTrials.gov ID, NCT02083484) was a global expanded access program that allowed access to pembrolizumab, an antiprogrammed death 1 antibody, for patients with advanced melanoma before its regulatory approval. Patients with unresectable stage III/IV melanoma that progressed after standard-of-care therapy, including ipilimumab and, if BRAF V600 mutant, a BRAF inhibitor, were eligible to receive pembrolizumab 2 mg/kg every 3 weeks. Response was assessed by immune-related response criteria by investigator review. Adverse events (AEs) were graded according to the National Cancer Institute Common Terminology Criteria for Adverse Events, version 4.0. In the United States, 979 patients enrolled between April and September 2014. Of the 947 evaluable patients, 621 (65.6%) remained on treatment and transitioned to receive commercial pembrolizumab following approval by the Food and Drug Administration, whereas 326 (34.4%) discontinued, most commonly for disease progression (39.6%) or death (26.4%). Objective response rate was 14.5% (95% confidence interval, 12.2%–16.8%) in the treated population (n=947) and 22.1% (95% confidence interval, 18.8%–25.5%) in patients who had ≥1 response assessment reported (n=619). Twelve patients achieved complete response. One hundred eighty-one (19.1%) patients experienced ≥1 treatment-related AE, most commonly general disorders (8.0%), skin/subcutaneous tissue disorders (7.3%), and gastrointestinal disorders (6.4%); 29 (3.1%) patients experienced ≥1 grade 3/4 treatment-related AE. Immune-mediated AEs were also reported. There were no treatment-related deaths. The safety and efficacy observed in this expanded access program were consistent with those previously reported for similar populations and support the use of pembrolizumab for patients with advanced melanoma.